2009
DOI: 10.1523/jneurosci.4780-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-9 Activation Revealed by Semaphorin 7A Cleavage Is Independent of Apoptosis in the Aged Olfactory Bulb

Abstract: Caspases are essential in multicellular organisms for inducing cell death during normal development and in the immune system. However, caspases can also trigger the degenerative process under certain conditions such as pathophysiological conditions and aging. Here, we identified Semaphorin 7A (Sema7A) as a novel substrate for caspase-9 that can be used to monitor caspase-9 activity in mice, and found nonapoptotic caspase-9 activation in the aged olfactory bulb (OB). Immunostaining of the OB for the caspase-9-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
(47 reference statements)
0
37
0
Order By: Relevance
“…Several families of axon guidance cues, including semaphorin 3a and Ephrin-As, have critical roles in the axonal wiring and the organization of the olfactory system. We have recently found that Sema7A, a membrane-anchored member of the semaphorin family of guidance proteins required for the proper formation of the lateral olfactory tract (13), is a substrate for caspase-9 (14). A rabbit polyclonal antibody against amino acid 1-100 of mouse Sema7A (Abcam) immunolabeled Sema7A specifically in caspase-9-activated cells (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several families of axon guidance cues, including semaphorin 3a and Ephrin-As, have critical roles in the axonal wiring and the organization of the olfactory system. We have recently found that Sema7A, a membrane-anchored member of the semaphorin family of guidance proteins required for the proper formation of the lateral olfactory tract (13), is a substrate for caspase-9 (14). A rabbit polyclonal antibody against amino acid 1-100 of mouse Sema7A (Abcam) immunolabeled Sema7A specifically in caspase-9-activated cells (14).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently found that Sema7A, a membrane-anchored member of the semaphorin family of guidance proteins required for the proper formation of the lateral olfactory tract (13), is a substrate for caspase-9 (14). A rabbit polyclonal antibody against amino acid 1-100 of mouse Sema7A (Abcam) immunolabeled Sema7A specifically in caspase-9-activated cells (14). To examine whether Apaf-1/caspase-9 signaling in OSN axons cleaved Sema7A during development, we performed immunofluorescent analysis of OB sections from WT, apaf-1-deficient, or caspase-9-deficient mice.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, given that the release of SEMA7A to the medium by cleavage of its GPI anchor has been demonstrated to be essential in some processes (24), further autocrine activation of transmigrated PMNs by solubilized SEMA7A might be possible (25). Taken together, endothelial SEMA7A rises as a potential therapeutic target for the treatment of hypoxia-induced inflammatory disorders in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic nature of semaphorins is particularly evident for Sema7A, whose roles in immune function [74] and cancer biology [75,76,77] have been extensively studied. In addition, a few reports have addressed its role in neuronal development [78,79,80,81,82]. A study performed in our laboratory has revealed a role for Sema7A and its two receptors, PlexinC1 and β 1 -integrin, in the regulation of GnRH cell motility [24].…”
Section: Semaphorin Expression and Role In The Development Of The Olfmentioning
confidence: 99%